2013
DOI: 10.1037/h0094745
|View full text |Cite
|
Sign up to set email alerts
|

Teaching recovery to medical students.

Abstract: The recovery teaching program was associated with increased knowledge of recovery principles and more positive attitudes toward mental illness. Psychiatric clinical placements for medical students should include an explicit recovery focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Clinical placements may improve students' skills (Henderson, Happell, & Martin, 2007;Martin & Happell, 2001); knowledge (Feeney, Jordan, & McCarron, 2013); attitudes toward people with mental health issues (Markström et al, 2009); and confidence to function in mental health settings (Bell, Horsfall, & Goodin, 1998;Ross, Mahal, Chinnapen, & Rana, 2013). They may reduce their fears and anxieties about working in mental health (Martin & Happell, 2001;Thomas & Bhattacharya, 2012) and increase their intentions to pursue careers in this specialty (Happell & Gaskin, 2013).…”
Section: Benefits Of Clinical Placementsmentioning
confidence: 94%
See 2 more Smart Citations
“…Clinical placements may improve students' skills (Henderson, Happell, & Martin, 2007;Martin & Happell, 2001); knowledge (Feeney, Jordan, & McCarron, 2013); attitudes toward people with mental health issues (Markström et al, 2009); and confidence to function in mental health settings (Bell, Horsfall, & Goodin, 1998;Ross, Mahal, Chinnapen, & Rana, 2013). They may reduce their fears and anxieties about working in mental health (Martin & Happell, 2001;Thomas & Bhattacharya, 2012) and increase their intentions to pursue careers in this specialty (Happell & Gaskin, 2013).…”
Section: Benefits Of Clinical Placementsmentioning
confidence: 94%
“…Undertaking placements in clinical environments may promote the acquisition of new knowledge (Feeney et al, 2013). In their comparison of medical students in psychiatry undertaking recovery-focussed placements with those in more traditional placements, Feeney and colleagues found that students in recovery-focussed placements understandably demonstrated greater knowledge of recovery principles.…”
Section: Benefits Of Clinical Placementsmentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical placements have also been found to reduce anxieties and fears of working in mental health settings and improve attitudes towards people living with mental illness (Feeney et al . ; Happell et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The SAMHSA Recovery-to-Practice project and related initiatives are making significant progress in this regard in the fields of psychiatry, psychiatric nursing, psychology, social work, addiction counseling, and peer support (Feeney, Jordan, & McCarron, 2013;Mueser, Silverstein, & Farkas, 2013;Rudnick & Eastwood, 2013;SAMHSA, 2013). The Psychiatric Rehabilitation Association Certified Psychiatric Rehabilitation Practitioner (CPRP) is a national credential that does not require a bachelor's degree.…”
Section: Peer Career Implications 341mentioning
confidence: 98%